Seed Banks - Colin Khoury - Radio New Zealand (2015)
The world's food sources are under pressure, from climate change, population growth and an over-reliance on a few key crops - rice, maize and wheat. If one of these crops were to fail we'd be in trouble, but there is an insurance policy - thousands of wild ancestor seeds, kept under lock and key, to call upon when we need to find genetic resistance to a new disease or pest. Colin Khoury is from the International Centre for Tropical Agriculture in Colombia and he joins us from Colorado.